Why Physiologically Cold weather can Increase Obesity Rates ? - Habibzadeh Nasim (International Physiology Journal, 2018)
Obesity generally accounts for a pathophysiology condition at which excessive body fats get accumulated in body parts. Among different - causes, ambient temperature such as cold environment can dramatically develop obesity in different individual. Cold weather influences the hormones that are related to the hunger and increases appetite toward overeating and subsequently inactivity . Controlling the calorie intakes through informative care are good strategies to prevent or govern obesity at any situation such as cold temperature
Keywords: Cold weather